Impact of Brand Preference Dimensions on Customer Satisfaction - A Meta Analysis for Passenger Cars - Dharmaraj, C. (Indian Journal of Marketing, 2010)
Consumer buying decision is a complex phenomenon. Selection of the product or services involves many processes. For the selection of durable products like cars, the customer has to spend much time to evaluate and choose the best based on their economic conditions and requirements. Before two decades, people had much leisure time, they used to spend their time as they liked. But after the opening up of the economy, people are so busy, they are not able to spend enough time to choose the right product or services as they wish. With the key issues, the researcher developed an interest to test the impact of brand preference dimension on customer satisfaction. This study reveals the factors that will influence the brand preference of passenger cars in India and addresses the impact of brand preference dimensions on customer satisfaction. Moreover, this study will be more relevant and useful for general public as well as the car users, manufacturers and dealers can understand the dimensions reflecting brand preference of passenger cars and impact of all these factors on customer satisfaction.